A Mobile Application Prototype Designed to Support Physical Therapy Assessment Learning Processes - Tavera Romero, Carlos Andrés; Jaramillo Losada, Jennifer; Díaz Velásquez, María Fernanda; Domínguez Pineda, Andrés Gerardo; Hurtado López, Victor Manuel (International Journal of Interactive Mobile Technologies (iJIM), 2023)
The present work is the result of applied research, which describes how the physical therapy program at the Universidad Santiago de Cali approached the support of the learning processes from the Guide to Physical Therapist Practice issued by the American Physical Therapy Association (APTA) from a teaching perspective using information technologies with an emphasis on mobile devices (D-Learning). The implementation process was conducted using the PSP (Personal Software Process) methodology, condensing its six characteristic moments to address the problem in four stages: planning, design, development, and validation, corresponding to phases 2 and 3 of the interdisciplinary project developed by and between the Schools of Engineering and Health Sciences, thereby understanding that the remaining phases exceed the scope of this paper (these phases include a systematic review, an analysis, and feedback from the academic community). A preliminary assessment describes the knowledge gathering and idea conception processes, as well as the solution design process in Enterprise Architect. Subsequently, the prototype was implemented, the corresponding documentation was prepared, and its usability was validated by the academic community at the university. Therefore, a supporting tool was generated, focusing specifically on learning about the Guide to Physical Therapist Practice.